Ursos ao vivo: masculinidades como prática de si no contexto online - Caroba, Pablo Vinicius Pizzelli (2021)
This research seeks to bring together two distinct themes: studies on masculinities and ethnography carried out in virtual or online environments. Doing ethnographic research on the GROWLr bear-only app, I tried to think of other ways of doing anthropology that weren't stuck in old concepts like “field” and how this can be rethought and reworked within these new ethnographic practices. The concept of “digital ethnography” was created approximately 20 years ago by Christine Hine (2001), who also thought about the limitations that the traditional ethnographic method found nowadays when taken only within its arrangements created in the 19th and 20th centuries. With the exponential growth in the possibility of accessing the internet and the consequent increase in the relationships that take place in these environments, this field has become increasingly relevant and often indispensable within contemporary anthropology. Afterwards, I sought to reflect on the theme of masculinities from the point of view of gender studies and observed the bears in three dimensions, taking as a reference point the foucauldian concept of "practice of the self", which is part of the “hegemony-alethurgy-practice of the self” trio, as formulated by the philosopher in his last courses at the Collége de France. Finally, I was able to conclude that the virtual environment seems at the same time to facilitate and encourage more pronounced “masculine” behavior and also seems to make people more comfortable to say what they really think by “hiding” the immediate figure of the listener.